Water-soluble chitosan derivatives and pH-responsive hydrogels by selective C-6 oxidation mediated by TEMPO-laccase redox system. (15th April 2018) - Botelho da Silva, Suse; Krolicka, Malgorzata; van den Broek, Lambertus A.M.; Frissen, August E.; Boeriu, Carmen Gabriela
Graphical abstract: Highlights: TEMPO-laccase oxidation is a new route to add aldehyde and carboxylate to chitosan. Oxidation mediated by TEMPO-laccase system improves chitosan solubility. A pH-responsive chitosan hydrogel can be formed by TEMPO-laccase oxidation. Chitosan hydrogel stabilization is due to self-crosslinking by dynamic imine bonds. Low COO- and CHO clusters allow crosslinking via imine bonds in oxidized chitosan. Abstract: Chitosan is a polysaccharide with recognized antioxidant, antimicrobial and wound healing activities. However, this polymer is soluble only in dilute acidic solutions, which restricts much of its applications. A usual strategy for improving the functionality of polysaccharides is the selective oxidation mediated by 2, 2, 6, 6-tetra-methyl-1-piperidinidyloxy (TEMPO) using laccase as a co-oxidant. In this work, the TEMPO-laccase redox system was used for the first time to selectively oxidize chitosan in order to produce tailored derivatives. The reaction was performed at pH 4.5 under continuous air supply and the oxidized products were characterized structurally and functionally. The TEMPO-laccase oxidation successfully added aldehyde and carboxylate groups to chitosan structure resulting in derivatives with oxidation between 4 and 7%. These derivatives showed increased solubility and decreased viscosity in solution. If chitosan is dissolved in diluted hydrochloric acid prior to TEMPO-laccase oxidation, a crosslinked chitosan derivative was produced, which was able to form a pH-responsive hydrogel.